Market Response to Policy Announcements: An Analysis of Capital Market Reactions to the Introduction of Battery Electric Vehicle Incentives in Indonesia (E-Jurnal Akuntansi, 2026)
Information entering the market can influence investor behavior, as reflected in abnormal returns and fluctuations in trading volume activity. This study aims to analyze the market's reaction to the announcement of Minister of Finance Regulation Number 38 of 2023. Drawing on the efficient market hypothesis, specifically the semi-strong form, this research employs an event study methodology over a 15-day window (t-7 to t+7). The sample consisted of 10 companies within the automotive and components subsectors, evaluated using one-sample t-tests, onesample Wilcoxon signed-rank tests, and paired-sample Wilcoxon signed-rank tests. The findings revealed significant abnormal returns and changes in trading volume activity surrounding the announcement. These outcomes suggest that the market perceived the announcement positively, significantly impacting investor reactions.
Keywords: Capital market reactions; Government regulations; Battery electric vehicle; Abnormal Return; Trading volume activity